Pengaruh Pewarnaan Beton Cetak Pada Dinding Serap Sebagai Selubung Bangunan Tinggi - Slamet Anambyah; Endang Setyowati (Forum Teknik, 2010)
AbstrakThe use of exterior building materials will indirectly affect the room temperature. Planners are  expected  to  choose  the type  of  building  materials  in  accordance  with  the  climate andbuilding conditions to produce good quality buildings. One alternative is to use absorbing wall as a building envelope. Absorbing wall is a kind of wall made of concrete plate with a certain thickness (in the study used a thick wall as 10 cm) that could reduce heat to not cause thermal effects on the environment and on the exterior of the building (Frick, 1998). To support the appearance and aesthetics of the building the walls absorb has coloured. Coloring the wall will affect the absorben surface of the wall to ward heat and indirectly affect the room temperature.Besides, the wall thickness and duration of heating also influence.The research method used was an experiment in the laboratory. Observations were madeby measuring temperature in the room which is divided into four stages of observation, of eachwithin 1.5 hours, six hours and one hour.The results showed that the walls absorb the color produced in the room temperature is higher than the outer space with a difference in temperature between 2-60 Celsius. This is due partly because the space is measured is a sealed space, no change of air in the morning and night, so  hot  that occurred  during  the  day  generated  by  the exterior  wall confined  in  the building. According to the standard of comfort at room temperature, the use of absorbtive wallcolor in these experiments included in the category uncomfortable.Keywords: absorbing wall color, building temperature, heat confined